Inactivation of Efflux Pumps Abolishes Bacterial Biofilm Formation - Kvist, Malin (American Society for Microbiology (ASM), 2008)
Bacterial biofilms cause numerous problems in health care and industry; notably, biofilms are associated with a large number of infections. Biofilm-dwelling bacteria are particularly resistant to antibiotics, making it hard to eradicate biofilm-associated infections. Bacteria rely on efflux pumps to get rid of toxic substances. We discovered that efflux pumps are highly active in bacterial biofilms, thus making efflux pumps attractive targets for antibiofilm measures. A number of efflux pump inhibitors (EPIs) are known. EPIs were shown to reduce biofilm formation, and in combination they could abolish biofilm formation completely. Also, EPIs were able to block the antibiotic tolerance of biofilms. The results of this feasibility study might pave the way for new treatments for biofilm-related infections and may be exploited for prevention of biofilms in general.